Impact of training on community health worker regarding newborn care - Nahrel, Rakesh; Kosam, Ajay; Thakur, Hemlata; Pandey, Sachin (Indian Journal of Child Health, 2015)
Background: In India, an estimated four million deaths occur each year in the neonatal period. Effective intervention at primary care level can prevent a large proportion of these deaths. Objective: To assess the impact of training on knowledge and skill regarding newborn care among Auxiliary Nurse Midwife (ANM). Methods: A total of 180 ANMs who attended skilled birth attendant training program under RCH were included in the study. The study was conducted over a period of 2 years from May 2013 to June 2015. A 14 training sessions each lasting for 15 days were conducted in 2 years and each session had a batch of 12-15 ANMs. They were assessed for the impact of training at the end of training on semi-structured and pretested schedule. Results: The knowledge of health workers related to the care of a newborn at birth was not adequate. An average of 94.8 ANMs responded correctly to pre-test questions whereas after training there was a significant improvement in the post-test score. After training an average of 160.5 ANMs (p=0.001) responded correctly. A mean of 84 ANMs had adequate knowledge related to danger signs in the neonatal period before training. Aftertraining significant number of ANMs (mean=156, p=0.002) responded correctly. Baseline knowledge related to feeding of the newborn was also inadequate (mean=120), but after training there was a significant improvement, 164 ANMs respond correctly (p=0.02). Conclusion: Knowledge of ANMs in the rural area regarding essential newborn care is inadequate. The training of health workers need to be remodeled and updated to improve neonatal outcome.